Scalpel versus electrosurgery: Comparison of gingival perfusion status using ultrasound Doppler flowmetry - N Manivannan; R S Ahathya; P C Rajaram (Wolters Kluwer Medknow Publications, 2013)
The main prerequisites of any surgical procedure are achievement of good visibility and access to the site with minimal bleeding and rapid and painless healing. With the advancement of technology the armamentarium for oral surgical procedures has also widened. The use of alternate methods to the traditional scalpel such as electrosurgery, laser, and chemicals has been widely experimented with. This article aims to report the gingival perfusion pre-operatively and post-operatively, comparing the use of scalpel and electrosurgery in different anatomic sites in patient. Since wound healing is influenced by its revascularization rate, which follows the pattern of new connective tissue formation, the perfusion status of the gingiva has been studied using ultrasound spectral Doppler. The results of our study show that there was 30% more blood flow by 7 th day, 19% more blood flow by 15 th day and 11% more blood flow by 30 th day in sites where the scalpel was used compared with sites where electrosurgery technique was used.